‘POTRET DIRI’ MELALUI SEMIOTIKA RIFFATERRE: PUISI JAHWASANG KARYA YOON DONGJU - Herlinda Yuniasti (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2019)
This article discusses the 'Self-portrait' in modern Korean poetry Jahwasang (hangul: 자화상) by Yoon Dongju using the Riffaterre’s semiotic theory. Semiotic theory assumes that literature is a semiotic fact of humanity. Semiotic means that literature is a collection of meaningful sign systems. The purpose of this study is to find the meaning of 'self portrait' written on Jahwasang. The research method of this study is a qualitative method. Based on the analysis, it can be concluded that poem "self portrait" is about Yoon Dongju’s reflection and introspection of the past.Keywords: Jahwasang; Riffaterre; Semiotics; Yoon Dongju